Polysaccharides influence human health via microbiota-dependent and -independent pathways - Gan, Liping; Wang, Jinrong; Guo, Yuming (Frontiers in Nutrition, 2022)
PPolysaccharides are the most chemically diverse molecules and can be extracted from abundant edible materials. Increasing research has been conducted to clarify the structure and composition of polysaccharides obtained from different materials and their effects on human health. Humans can only directly assimilate very limited polysaccharides, most of which are conveyed to the distal gut and fermented by intestinal microbiota. Therefore, the main mechanism underlying the bioactive effects of polysaccharides on human health involves the interaction between polysaccharides and microbiota. Interest in the role of polysaccharides in gut health, obesity, and related disorders has recently increased due to the wide range of valuable biological activities of polysaccharides. The known roles include mechanisms that are microbiota-dependent and involve microbiota-derived metabolites and mechanisms that are microbiota-independent. In this review, we discuss the role of polysaccharides in gut health and metabolic diseases and the underlying mechanisms. The findings in this review provide information on functional polysaccharides in edible materials and facilitates dietary recommendations for people with health issues. To uncover the effects of polysaccharides on human health, more clinical trials should be conducted to confirm the therapeutic effects on gut and metabolic disease. Greater attention should be directed toward polysaccharide extraction from by-products or metabolites derived from food processing that are unsuitable for direct consumption, rather than extracting them from edible materials. In this review, we advanced the understanding of the structure and composition of polysaccharides, the mutualistic role of gut microbes, the metabolites from microbiota-fermenting polysaccharides, and the subsequent outcomes in human health and disease. The findings provide insight into the proper application of polysaccharides in improving human health.